Molecular phylogeny of stream treefrogs (Hylidae: Hyloscirtus bogotensis Group), with a new species from the Andes of Ecuador - Guayasamín, Juan (2015)
We present a new molecular phylogeny of the stream treefrog genus Hyloscirtus, with an improved taxon sampling in the Hyloscirtus bogotensis group. The tree supports the existence of three clades within the genus (Hyloscirtus armatus group, H. bogotensis group and Hyloscirtus larinopygion group) in congruence with previous studies, and suggests the presence of at least three new species in the H. bogotensis group. Herein, we describe one of these species, Hyloscirtus mashpi n. sp. from the Pacific slope of the Ecuadorian Andes. The validity of the latter is supported by molecular, morphological and acoustic data. We also tested individuals of the new species for the chytrid fungus Batrachochytrium dendrobatidis, finding a prevalence of 17.6% (6 positives and 28 negatives). However, at sampled streams, frog densities were high, suggesting that H. mashpi n. sp. may be tolerant to the infection. © 2015, © 2015 The Author(s). Published by Taylor & Francis.